Do social marketing campaigns in health work? A critical analysis of four UK campaigns - Coope, David (2007)
This management project looks at four recent social marketing campaigns in the field of health in the UK to determine whether such campaigns work. The project critically analyses the marketing campaigns used, and aims to determine the range of factors that create a successful social marketing campaign in health.